Complex interplay between type 2 diabetes mellitus and pancreatic cancer: insights from observational and mendelian randomization analyses - Yuxin Wang; Lu Xie; Ye Gu; Hangbin Jin; Jianfeng Yang; Qiang Liu; Xiaofeng Zhang (BMC Cancer)
Abstract Background To investigate the causal relationship between type 2 diabetes mellitus (T2DM), pancreatic cancer (PC) risk and identify the mediating effects of various risk factors on that relationship. Methods 581 PC patients and 582 healthy controls who visited our center from January 2013 to December 2023 were included in this retrospective study. Multivariable logistic regression was performed to evaluate the association between T2DM and PC through odds ratios (ORs) and 95% confidence intervals (CIs). Mendelian randomization (MR) studies were then conducted to explore the causal relationship between T2DM and PC, and causal mediation analysis (CMA) to examine the mediating role of common risk factors. Results After adjusting for confounding factors, retrospective analysis revealed significant association between new-onset diabetes mellitus (NODM) and PC risk, with insulin treatment also linked to increased PC development. The standard inverse-variance weighted (IVW) method indicated that genetic susceptibility to T2DM was associated with an increased risk of developing PC (OR = 1.11; 95% CI = 1.034–1.193). Furthermore, MR showed T2DM, insulin treatment, FGF-4, and sulfhydryl oxidase 2 may be independently associated with the prevalence of PC. Specially, CMA demonstrated that insulin treatment, FGF4, and sulfhydryl oxidase 2 mediate the pathway from T2DM to PC, contributing 56.8%, 55.8%, and 5.9% of the total effect, respectively. Conclusion This study supports the association between T2DM, specifically NODM, and increased PC risk, with insulin therapy, FGF4, and sulfhydryl oxidase 2 mediating this pathway. Further research is required to elucidate the mechanisms underlying these mediating effects. Clinical trial number not applicable.